DESCRIPTIVE ANALYSIS OF 2022 FIFA WORLD CUP MATCH RESULTS IN QATAR: ANALISIS DESKRIPTIF HASIL PERTANDINGAN PIALA DUNIA FIFA DI QATAR TAHUN 2022 - Putro, Olimpik Reski Sholeh Eko (Kesehatan Olahraga, 2023)
Football is a highly popular sport among the general public. This sport consists of 11 players per team. Like other sports, football has a global governing body, which is FIFA (Federation Internationale de Football Association). FIFA, as the governing federation of football, organizes various official competitions, one of the most popular being the FIFA World Cup. This competition has been held 21 times since its first edition in 1930. The World Cup is held every 4 years. The last World Cup took place in 2022, with Qatar being selected as the host country. The 2022 FIFA World Cup was contested by 32 nations that had previously qualified through the World Cup qualifiers.Argentina emerged as the world champion by defeating France in the Grand Final match through a penalty shootout with a score of 4-2, followed by Croatia securing the third place by defeating Morocco with a score of 2-1. Besides the World Cup title, several individual awards were received by players, including Top Scorer by Kylian Mbappe (France), Golden Boot/Best Player by Lionel Messi (Argentina), Golden Gloves/Best Goalkeeper by Emiliano Martinez (Argentina), and Best Young Player by Enzo Fernandez (Argentina).In this research, a descriptive analysis was conducted to examine the performance of each national team in the 2022 World Cup. The results of the descriptive analysis revealed that the team with the highest average ball possession per match was Spain with a percentage of 69%. The team with the highest average goals scored per match was England with 2.6 goals per match, and the team with the highest average number of attempted attacks was Germany with 22.33 attempts per match.) Keywords: Descripstion Analytics, FIFA World Cup 2022, Football